Key economic factors influencing emergency department crowding in Saudi Arabia - Almulhim, Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze healthcare workers' perception of ED crowding, its economic burden, insurance challenges, and infrastructure restrictions, while analyzing role-based variances in these perspectives. A cross-sectional online survey was conducted among 889 healthcare professionals throughout all 13 administrative regions of Saudi Arabia. Participants included nurses, physicians, pharmacists, administrative workers, and allied health professionals. Descriptive and inferential statistics (chi-square tests) were employed to examine and identify differences based on professional roles. Key findings highlighted broad concerns regarding ED crowding, with 72.5% of respondents observing high patient volumes waiting for diagnostic results. Significant economic challenges were observed, including high out-of-pocket expenditures (48.2% agreement) and inadequate insurance coverage for routine care (41.8%). Infrastructure challenges, such as bed shortages (65.0%) and insufficient staff (69.3% for nurses, 74.0% for physicians), were important problems. Statistically significant differences found across roles: nurses encountered staffing and resource shortages more acutely, whereas physicians underlined financial pressures on patients. The study underlined systemic misalignments in Saudi Arabia’s healthcare financing and infrastructure, contributing to ED crowding. Targeted actions, such as expanding insurance coverage, boosting primary care access, and addressing workforce shortages, are urgently needed. These findings align with Vision 2030 goals and give actionable insights for policymakers to promote emergency care efficiency and equity.